PROMOTING LEARNING AUTONOMY THROUGH SELF-ACCESS CENTER ACITIVITIES - Isry Laila Syatroh; Hendra Husnussalam (Jurnal Ilmiah P2M STKIP Siliwangi, 2017)
This paper attempts to shed some light on the activities and facilities in one Self-Access Center (SAC) in one university in Bandung. On the ground of this investigation, a context description of SAC in university levels is put forward followed by an overt statement of the objectives and the rationales of the study. There are three research problems being investigated: What is the typology of the SAC? What are the self-access language learning (SALL) activities and materials provided in this SAC? And how do the students perceive the self-access language learning (SALL) activities and materials? This qualitative study reveals that this SAC is categorized into supermarket typology of SAC. This is because of the SAC system offers learners the chance to look around and choose what they want to study. This system displays materials under clearly marked categories like in supermarket. This typology of SAC is suitable for all learner contexts (Gardner and Miller, 2008). However, this SAC still lack the materials and activities for SALL. Further development, in terms of materials and activities which can promote learning autonomy should be done. Most students (72%) perceive positively about certain SAC facilities, such as books, resources, strong internet connection, and cozy environment of reading and writing area. However, there should be more improvement in certain SAC facilities (such as rooms for consultation with SAC tutor, TV viewing area) and certain SAC activities (such as English club and native speaker contact).Keywords: autonomy, self-access center (SAC), self-access language learning (SALL)